The P Process - Five Steps to Strategic Communication - and HCCC (Johns Hopkins University)
The P Process is one of the most respected tools used in designing SBCC programs. Developed in 1982, the P Process is a tool for planning strategic, evidence-based health communication programs. More than thirty years later, communication professionals around the world are using the P Process to design, implement, monitor, and evaluate communication strategies, materials, and programs. The P Process is a step-by-step roadmap that can guide you from a loosely defined concept about changing behavior to a strategic and participatory program that is grounded in theory and has measurable impact. This update of the P Process incorporates lessons learned and acknowledges the real-time, dynamic nature of the strategic process as well as new technologies and the constantly changing nature of communication, social norms, individual behavior, and decision-making. It draws from many other disciplines, including design theory, behavioral economics, social psychology, and anthropology. At its essence though, the P Process is a tool that is only as useful as the data and thinking that go into each step. The attached file contains both the English and French versions.